2012
DOI: 10.1002/cplu.201100074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stability of Highly Crystalline and Stable Iron/Iron Oxide Core/Shell Nanoparticles for Biomedical Applications

Abstract: Biocompatible iron nanoparticles exhibiting a high magnetic moment are potentially useful for a variety of biomedical applications. However, once exposed to air, iron nanoparticles partially oxidize, effectively reducing their magnetic performance. Here, near‐monodisperse iron nanocrystals were synthesized and oxidized on the surface to form iron/iron oxide core/shell nanoparticles. The presence of excess stabilizers was shown to stabilize the core/shell nanoparticles, thus preventing further oxidation. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…All the mice were in good condition, which suggested that injected MNPs do not possess tumorigenic activity, and may not exert any acute toxic effects on the recipient. Therefore, it may be inferred that these MNPs can serve as an effective contrast agent, suitable for MRI .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the mice were in good condition, which suggested that injected MNPs do not possess tumorigenic activity, and may not exert any acute toxic effects on the recipient. Therefore, it may be inferred that these MNPs can serve as an effective contrast agent, suitable for MRI .…”
Section: Resultsmentioning
confidence: 99%
“…All the mice were in good condition, which suggested that injected MNPs do not possess tumorigenic activity, and may not exert any acute toxic effects on the recipient. Therefore, it may be inferred that these MNPs can serve as an effective contrast agent, suitable for MRI (32,33). These images indicated that, after injection of iron oxide, the signal intensity of the solid tumor group was lower than that of the control group.…”
Section: Tumorigenic Assessmentmentioning
confidence: 94%
“…[1][2][3][4] For the effective application of magnetic nanoparticles, fine and reproducible size control is essential. [5][6] For example, a number of biomedical applications (e.g., magnetic relaxometry, 7-8 magnetic particle imaging (MPI), [9][10] magnetic hyperthermia [11][12] ) rely on the superparamagnetic relaxation of magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Typically, iron oxide based nanoparticles have been increasingly used in a broad range of applications, for example, as contrast agents in magnetic resonance imaging (MRI), [6,7] targeted drug delivery, [6] electrochemical and biosensors [8][9][10] and as electrode materials for semiconductor gas sensors. [1][2][3][4][5][6] Typically, iron oxide based nanoparticles have been increasingly used in a broad range of applications, for example, as contrast agents in magnetic resonance imaging (MRI), [6,7] targeted drug delivery, [6] electrochemical and biosensors [8][9][10] and as electrode materials for semiconductor gas sensors.…”
Section: Introductionmentioning
confidence: 99%